Pengaruh Konsumsi Telur Rebus dan Jus Jambu Biji Merah terhadap Peningkatan Kadar Hemoglobin pada Remaja Putri dengan Anemia Ringan - Adinda Bella Annisya; Putri Agus Febriyani; Fenni Valianda; Aida Sa’adah; Yellin Cappiokta; Marice Sinorita; Dwi Jayanti Ramadhani; Bella Amalia Putri; Ni Putu Indrawati; Sri Pangestuti (NERSMID : Jurnal Keperawatan dan Kebidanan, 2025)
Adolescent girls are one of the groups that are susceptible to anemia because their iron needs are 3 times greater than men. One action that can be taken to meet iron needs is to consume boiled eggs and red guava juice because they have a nutritional content rich in iron, protein and vitamin C. The purpose of this study was to determine the effect of consuming boiled eggs and red guava juice on increasing hemoglobin levels in adolescent girls with mild anemia in the Cipaku Health Center Work Area in 2025. This study used a qualitative research design with a case study approach. The research sample was 8 adolescent girls aged 12-15 years who had mild anemia (11.0 g / dL - 11.9 g / dL) who were divided into 2 groups. Then an intervention was given in the form of consuming 2 boiled eggs to 4 adolescent girls and 250ml of red guava juice to 4 adolescent girls for 7 days. The results of the study showed that the increase in hemoglobin levels in 4 teenage girls who were given boiled eggs was 1.35 g/dL while the increase in hemoglobin levels in 4 teenage girls who were given red guava juice was 0.825 g/dL. The comparison results showed that boiled eggs were more effective in increasing hemoglobin levels compared to red guava juice. Based on these results, it can be concluded that there was an increase in hemoglobin levels in teenage girls who were given boiled eggs and red guava juice.